Posterior insular GABA levels inversely correlate with the intensity of experimental mechanical pain in healthy subjects - Thiaucourt, Margot; Shabes, Polina; Sack, Markus; Baumgärtner, Ulf; Schmahl, Christian; Ende, Gabriele (Neuroscience, 2018)
This study aimed to investigate the relation of GABA and glutamate levels in the posterior insula and mechanical pain sensitivity in healthy subjects. Nineteen healthy female individuals underwent single voxel magnetic resonance spectroscopy (MRS) at 3T. Metabolites were measured in the right posterior insula using MEGA-PRESS spectral editing. Mechanical pain sensitivity was experimentally assessed with pinprick stimuli on a numeric rating scale. Ratings of perceived intensity of 256mN and 512mN pinprick stimuli were negatively correlated with GABA levels and positively with glutamate levels in the posterior insula. Pinprick pain ratings were also positively correlated with the glutamate/GABA ratio. No significant correlation for pinprick stimuli of lower forces than 256mN was observed. The results of our study support the hypothesis that excitatory and inhibitory neurotransmitter levels and/or the ratio of glutamate/GABA levels in the posterior insula are related to individual differences in pain sensitivity. These results are in line with chronic pain studies, where elevated glutamate/GABA ratios in the insular cortex of patients with chronic pain syndromes were observed.